Control of Rest:Activity by a Dopaminergic Ultradian Oscillator and the Circadian Clock - Bourguignon, Clément; Storch, Kai-Florian (Frontiers in Neurology, 2017)
There is long-standing evidence for rhythms in locomotor activity, as well as various other aspects of physiology, with periods substantially shorter than 24hrs in organisms ranging from fruit flies to humans. These ultradian oscillations, whose periods frequently fall between 2 to 6hrs, are normally well integrated with circadian rhythms, however they often lack the period stability and expression robustness of the latter. An adaptive advantage of ultradian rhythms has been clearly demonstrated for the common vole, suggesting that they may have evolved to confer social synchrony. The cellular substrate and mechanism of ultradian rhythm generation have remained elusive so far, however recent findings – the subject of this review- now indicate that ultradian locomotor rhythms rely on an oscillator based on dopamine, dubbed the dopaminergic ultradian oscillator (DUO). These findings also reveal that the DUO period can be lengthened from <4 to >48hrs by methamphetamine treatment, suggesting that the previously described methamphetamine-sensitive (circadian) oscillator (MASCO) represents a long-period manifestation of the DUO.